MicroRNA-106a Inhibits Autophagy Process and Antimicrobial Responses by Targeting ULK1, ATG7, and ATG16L1 During Mycobacterial Infection - Liu, Kunmei; Hong, Dantong; Zhang, Fan; Li, Xin; He, Meng; Han, Xuebo; Zhang, Guolin; Xu, Guangxian; Stonehouse, Nicola J.; Jiang, Zhongjia; An, Weijun; Guo, Le (Frontiers in Immunology, 2021)
Autophagy is a key element of innate immune response against invading pathogens including Mycobacterium tuberculosis (M. tuberculosis). The emerging roles of microRNAs in regulating host antimicrobial responses against M. tuberculosis have gained widespread attention. However, the process by which miRNAs specifically influence antibacterial autophagy during mycobacterial infection is largely uncharacterized. In this study, we demonstrate a novel role of miR-106a in regulating macrophage autophagy against M. tuberculosis. H37Ra infection leads to downregulation of miR-106a in a time- and dose-dependent manner and concomitant upregulation of its three targets (ULK1, ATG7 and ATG16L1) in THP-1 macrophages. MiR-106a could inhibit autophagy activation and antimicrobial responses to M. tuberculosis by targeting ULK-1, ATG7 and ATG16L1. Overexpression of miR-106a dramatically inhibited H37Ra-induced activation of autophagy in human THP-1 macrophages, whereas inhibitors of miR-106a remarkably promoted H37Ra-induced autophagy. The inhibitory effect of miR-106a on autophagy process during mycobacterial infection was also confirmed by Transmission Electron Microscope (TEM) observation. More importantly, forced expression of miR-106a increased mycobacterial survival, while transfection with miR-106a inhibitors attenuated the survival of intracellular mycobacteria. Taken together, these data demonstrated that miR-106a functioned as a negative regulator in autophagy and antimicrobial effects by targeting ULK1, ATG7 and ATG16L1 during M. tuberculosis infection, which may provide a potential target for developing diagnostic reagents or antibacterials against tuberculosis.